Laboratory diagnosis of Epstein Barr Virus in diffuse large B cell lymphoma - Naidoo, Sharlene (My University, 2017)
Aims and objectives The study design aimed to assess and validate various laboratory techniques in the detection of EBV in HIV positive patients with diffuse large B cell lymphoma. The sensitivity and specificity of each technique was determined, as was the presence of an asymptomatic (latent) or lytic phase infection and the viral strain. DLBL samples occurring in HIV seropositive patients were used as a vehicle for these laboratory procedures which included chromogenic in situ hybridisation (EBER), immunohistochemistry (EBNA 2, LMP 1), real time PCR, (EBNA 1, LMP 2 and BZLF 1) and nested PCR (EBNA 2). Materials and Methods 46 cases of previously diagnosed DLBL from HIV positive individuals were identified and retrieved from the archives of the Department of Anatomical Pathology of the University of Witwatersrand and NHLS. All in-situ hybridisation, immunohistochemical and PCR laboratory procedures were carried out in accordance with the Standard Operating Procedures of the Anatomical Pathology Molecular Laboratory, using appropriate negative and positive controls throughout. Ethical clearance was obtained (M140273). Results/Conclusion A 20% frequency of EBV in HIV positive DLBL cases was established. All EBV infections were found to be in the lytic phase, with an almost equal distribution of latency patterns II and III and an equal distribution of EBV strains 1 and 2. EBER in situ hybridisation was confirmed to be the most sensitive and reliable method of viral detection, and the presence of the BZLF 1 gene determined by real time PCR was found to be a reliable indicator of a lytic infection.
A dissertation submitted to the Faculty of Health Sciences, University of Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science in the branch of Anatomical Pathology. 21 July 2017.
Keywords: Epstein-Barr Virus Infections; HIV; Lymphoma, Large B-Cell, Diffuse